Pathways to Working Alliances: Special Educators' Emotional Labor and Relationships with Students with Emotional and Behavioral Disorders. Issue 7 (July 2019) - Valenti, Michael; Brown, Elizabeth Levine; Horner, Christy Galletta; Mahatmya, Duhita; Colditz, Jason
Background/Context: Research has also shown that educators who are more socially and emotionally competent are more likely to create nurturing relationships and high-quality classroom environments that result in more academic success for students. Despite the importance of teacher-student relationships on student outcomes, limited research has investigated factors that contribute to development of these relationships, particularly for special education teachers (SETs) working with students with emotional/behavioral disorders (EBDs). Focus of Study: This study explores educators' emotions in the classroom through emotional labor theory, a framework for understanding how employees engage in the deliberate suppression or expression of emotions to achieve an organization's goals. We empirically investigate the potential connections between SETs' perceptions of their administrators' expectations about emotional displays, SETs' emotional acting strategies, and teacher-student relationships. Setting: This study was conducted within three schools in Western Pennsylvania serving students with EBDs in self-contained classrooms. Participants: Participants included SETs (N = 61) serving K–12 students who have been identified as having EBDs. SET demographics were as follows: 75% female, average age 32 (range 23–51), and 97% Caucasian. Participants averaged 4.62 years of teaching experience with the study site. Research Design: All SETs reported on their perceptions of emotional labor and their working alliances with each of their students in the fall semester. Students were nested within teachers, so we used multilevel path analyses to estimate mediational effects of emotional display rules and emotional acting on the teacher-student working alliance. Results: The results of this study suggest important connections between SETs' perceptions of emotional display rules, their use of emotional acting strategies, and their working alliances with students with EBDs. Specifically, SETs' reported perceptions of negative display rules affected how they engaged in surface acting when interacting with students. SETs' ratings of surface acting were associated with their working alliance tasks scores. Conclusions/Recommendations: These findings confirm recent research showing that educators engage in emotional acting and that some dimensions of this acting contribute to their relationships with students. Our findings may also suggest that surface acting is an acceptable emotional acting strategy that supports SETs' relationships with students. Because the emotional labor research in special education has yet to extrapolate on what display rules lead to the emotional acting strategies that the organization desires, how we make these rules more explicit could help teachers establish more sensibility regarding this area of their job.